Longitudinal Variation of EEJ Current during Different Phases of Solar Cycle. (May 2017) - Ismail, W N I; Hamid, N S A; Abdullah, M; Yoshikawa, A; Uozumi, T
Abstract: The equatorial electrojet (EEJ) is an eastward current flow around the dip equator in E-region of the ionosphere within the range of 90 to 120 km altitude. The longitudinal variation of EEJ was studied using the ground-based measurement from six different longitudinal sectors. The ground magnetometer data were provided by magnetometer networks such as those from Magnetic Data Acquisition System (MAGDAS) /Circum-pan Pacific Magnetometer Network (CPMN), Indian Institute of Geomagnetism (IIG) and International Real-time Magnetic Observatory Network (INTERMAGNET). The EUEL index used in this study was calculated from geomagnetic northward H component. The H-component was normalized to the dip equator using the CM4 model. This study present results of the longitudinal variation of EEJ during the three phases of solar cycle 24: solar minimum (2008), inclination phase (2011) and solar maximum (2014). Results show that EEJ current is higher in the American sector and lowest between African and Indian sector in 2008 and 2011. On the other hand, during the year of solar maximum, this current component is comparable in American and Southeast Asian sector.